The Role of Social Communication Networks in Mobilizing The Palestinian Public Opinion Toward Socio-Political Change - Zuhair Abed (My University, 2012)
The Internet invades all aspects of life, thereby contributing to the change in various phases of life in a record time. On the sidelines of this great event, a set of different phenomena has emerged at several levels. The spread of social communication networks is one of the most remarkable achievements in this day and age. Social networks play a vital role in forming the world public opinion, especially the Palestinians in their social and political issues. The study related to descriptive research is concerned with the reality of social communication networks. It also deals with the analysis and interpretation of events, phenomena, attitudes, and opinions to determine their impact on the Palestinian public opinion and socio-political change. This aims at correcting, updating and developing the reality through a survey approach covering a representative sample of (500) students (male & female) of Palestinian Universities in the Gaza Strip, who commonly use the internet and social communication networks. The most important findings of the study are: Email is the most commonly used, done at home three hours a day. The degree of confidence is average. The variables of gender and residence have no effect on the role of social communication networks in mobilizing the public opinion towards social and political change, whereas there is an effect of both university and specialization variables.

أخذ الإنترنت يغزو كل مرافق الحياة، مما أسهم في تغيير أوجه الحياة المختلفة في زمن قياسي، وقد ظهرت على هامش هذا الحدث مجموعة من الظواهر المختلفة على عدة مستويات، من أهمها: انتشار شبكات التواصل الاجتماعي التي تعُد إنجازاً ملموساً من الإنجازات الخلاقة في هذا العصر. ومن خلال متابعة تطور الدور الذي تقوم به شبكات التواصل الاجتماعي في تشكيل الرأي العام لدى الشعوب عامة، والشعب الفلسطيني خاصة، وطرح قضاياه الاجتماعية والسياسية. تأتي هذه الدراسة التي تنتمي إلى البحوث الوصفية لتدرس واقع شبكات التواصل الاجتماعي، وتناولها للأحداث والظواهر والمواقف والآراء، وتحليلها وتفسيرها لمعرفة تأثيرها على الرأي العام الفلسطيني، ومدى قدراتها على إحداث تغيير اجتماعي وسياسي، وذلك بغرض الوصول إلى استنتاجات تفيد الواقع إما بتصحيحه، أو تحديثه أو استكماله أو تطويره. وقد استخدم الباحث المنهج المسحي لعينة مكونة من (500) طالب وطالبة من طلاب الجامعات الفلسطينية في قطاع غزة، وهم من أكثر فئات المجتمع الفلسطيني استخداماً للانترنت، وشبكات التواصل الاجتماعي. ومن أهم النتائج التي خلصت إليها الدراسة: أن أكثر شبكات التواصل الاجتماعي استخداماً هو البريد الالكتروني، ويتم ذلك في المنزل في حدود ثلاث ساعات يومياً، وأن مدى الثقة فيها متوسط، وأنْ لا تأثير لكل من متغيريْ الجنس والسكن على دور تلك شبكات في تعبئة الرأي العام سياسياً واجتماعياً، في حين أسفرت النتائج عن وجود تأثيراً لكل من متغيريْ الجامعة والتخصص العلمي.
دور شبكات التواصل الاجتماعي في تعبئة الرأي العام الفلسطيني نحو التغيير الاجتماعي والسياسي - دراسة وصفية تحليلية